2011
DOI: 10.1088/0004-637x/736/2/91
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar Solid Hydrogen

Abstract: We consider the possibility that solid molecular hydrogen is present in interstellar space. If so cosmic-rays and energetic photons cause ionisation in the solid leading to the formation of H + 6 . This ion is not produced by gas-phase reactions and its radiative transitions therefore provide a signature of solid H 2 in the astrophysical context. The vibrational transitions of H + 6 are yet to be observed in the laboratory, but we have characterised them in a quantum-theoretical treatment of the molecule; our … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…He concluded that electrical charging processes stabilize H 2 grain surfaces even at temperatures where, usually, the volatility of H 2 is already very high (10 K). Lin et al (2011) proposed to track H 6 + as a probe for the presence of solid H 2 . Bernstein et al (2013) proposed the presence of contaminated CHIMPs.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…He concluded that electrical charging processes stabilize H 2 grain surfaces even at temperatures where, usually, the volatility of H 2 is already very high (10 K). Lin et al (2011) proposed to track H 6 + as a probe for the presence of solid H 2 . Bernstein et al (2013) proposed the presence of contaminated CHIMPs.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…Astronomers have been interested in solid H 2 in the ISM (Lin et al 2011) since the late 1960s . In addition to the few layers adsorbed on water ice mentioned earlier, the presence of solid H 2 was proposed as flakes (Pfenniger & Puy 2003) or as H 2 dust stabilised by an electric field (Walker 2013), forming contaminated H 2 clusters (Bernstein et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed models of the cosmic-ray induced chemistry in our clouds would not be easy to construct, despite their simple composition, because of the additional complexities that are introduced by H 2 condensation. We note in particular the following points: ionisation of the condensed H 2 favours the production of H + 6 , rather than H + 3 (which dominates in gas-phase) (Lin, Gilbert and Walker 2011); clusters of H 2 ligands may form around any ions (Duley 1996;Bernstein, Clark and Lynch 2013); electrons and ions that encounter snowflakes will tend to stick on the surface, or in the bulk of the snowflake (Walker 2013); and at present the relevant reaction rates in or on the condensed H 2 are largely unknown.…”
Section: Reconciliation With Mckee's Critiquementioning
confidence: 90%
“…There are other direct and indirect ways to detect H 2 , as described in Combes & Pfenniger (1997), but most of them only apply for gaseous H 2 . Lin et al (2011) argue that H + 6 detection would indicate solid H 2 , as this ion is not formed by gas-phase reactions.…”
Section: Introductionmentioning
confidence: 98%